Digital Transformation of Multidisciplinary Design Firms A Systematic Analysis-Based Methodology for Organizational Change Management - Bonanomi, Marcella M. (PoliMI SpringerBriefs,, 2019)
The book brings forth a better understanding of what process-oriented and organizational changes occur in Architecture, Engineering and Construction firms, how they unfold in context, and what change management strategies can be developed to plan and lead a digital business transformation accordingly. It develops a systematic, analysis-based approach to change management for supporting the digital transition which is made up by the following components: change management framework for identifying primary areas of investigation; set of change analysis methods for analyzing and visualizing process-oriented and organizational changes through qualitative and quantitative assessments; and strategic lines and related action-based approaches for managing change in the design process and organizational structures. The book represents one of the first comprehensive reviews of change management and digital practice, and provides case studies which extend the understanding of change management in the context of the digitalization and will benefit both industry practitioners and researchers.